Resin composition, laminate and printed circuit board
Patent Information
- Application Number
- TW114109233
- Authority / Receiving Office
- TW · TW
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-12
- Publication Date
- 2026-09-16
- Estimated Expiration
- 2045-03-11
AI Technical Summary
Existing resin compositions for circuit boards suffer from resin agglomeration, flow marks, and inadequate performance parameters such as glass transition temperature (Tg), coefficient of thermal expansion (CTE), and copper foil tensile strength, which are critical for high-frequency, high-speed applications.
A resin composition comprising unsaturated polyphenylene ether resin, styrene-butadiene-styrene copolymer, hydrogenated polyolefin resin, vinyl elastomer copolymer, and a crosslinking agent with a specific ratio of diisopropylbenzene crosslinking agent, enhancing mechanical and thermal properties.
The composition improves appearance, eliminates resin agglomeration, achieves a Tg ≥180°C, CTE ≤14 ppm/°C, and copper foil tensile strength ≥3.0 lb/in, meeting stringent performance requirements for high-frequency circuit boards.
Smart Images

Figure TWG2TA001075875_001 
Figure TWG2TA001075875_002 
Figure TWG2TA001075875_003
Abstract
Description
[Technical Field]
[0001] This invention relates to a resin composition, a laminate, and a printed circuit board, and particularly to a resin composition used in the manufacture of copper-clad laminates and prepregs for PCB circuit boards. [Previous Technology]
[0002] Advances in information processing technology have propelled digital circuits into a stage of high-speed information processing and high-frequency signal transmission. To meet the demands of high-speed information transmission, low-dielectric resin materials have gradually become the main development direction for high-frequency and high-speed transmission substrates.
[0003] With the increasing integration of electronic components per unit area, the requirements for circuit board processing performance are becoming increasingly stringent. Resin materials must possess high reliability, high heat resistance, and high dimensional stability to ensure their long-term stability and service life in high-frequency and high-speed application environments. In addition, as the substrate usage environment becomes increasingly harsh, higher requirements are also placed on the strength and heat resistance of resin materials to ensure that the materials remain stable under mechanical stress and high-temperature conditions.
[0004] In the prior art, resin compositions are prone to resin agglomeration inside the circuit board after lamination and filling, and flow marks often appear on the surface of the circuit board, resulting in unstable substrate quality. In addition, in order to further improve the overall performance of the substrate, the glass transition temperature (Tg) and coefficient of thermal expansion (CTE) of the material have also become key parameters.
[0005] Based on the above performance requirements, the development of low dielectric loss resin materials needs to simultaneously optimize multiple characteristics such as copper foil tensile strength, heat resistance, Tg, and CTE to meet the stringent requirements of modern electronic components. Accordingly, how to improve the composition to avoid resin agglomeration and flow patterns and obtain better finished product characteristics has become one of the important issues in this field. [Summary of the Invention]
[0006] The main objective of this invention is to provide a resin composition comprising 100 parts by weight of the total weight of the resin composition, the resin composition comprising: (A) 20 to 40 parts by weight of unsaturated polyphenylene ether resin; (B) 5 to 15 parts by weight of styrene-butadiene-styrene copolymer; (C) 10 to 20 parts by weight of hydrogenated polyolefin resin; (D) 10 to 20 parts by weight of vinyl elastomer copolymer; and (E) 20 to 40 parts by weight of crosslinking agent; wherein the crosslinking agent comprises 10 to 30 parts by weight of diisopropylbenzene crosslinking agent, and the diisopropylbenzene crosslinking agent is composed of 75% to 80% of 1,3-diisopropylbenzene and 20% to 25% of 1,4-diisopropylbenzene.
[0007] In one embodiment of the present invention, the crosslinking agent may include a vinyl crosslinking agent as required, and the ratio of the diisopropylbenzene crosslinking agent to the vinyl crosslinking agent is 2.9:0.1 to 1:2.
[0008] In one embodiment of the present invention, the vinyl crosslinking agent is selected from at least one of the group consisting of divinylbenzene (DVB), bis(vinylbenzyl) ether (BVBE) or 1,2-bis(vinylphenyl)ethane (BVPE).
[0009] In one embodiment of the present invention, the hydrogenated polyolefin resin is selected from at least one of the group consisting of hydrogenated styrene-butadiene-styrene triblock copolymers and hydrogenated styrene-butadiene-styrene triblock copolymers substituted with maleic anhydride.
[0010] In one embodiment of the present invention, the vinyl elastomer copolymer is selected from at least one of the group consisting of polybutadiene, styrene-butadiene copolymer (SBR), styrene-butadiene-styrene block copolymer (SBS), polyisoprene, styrene-isoprene copolymer, styrene-isoprene-styrene block copolymer (SIS), acrylonitrile-butadiene copolymer, and acrylonitrile-butadiene-styrene block copolymer.
[0011] In one embodiment of the present invention, the resin composition further comprises: a free radical initiator selected from at least one of the group consisting of azobisisobutyronitrile, 2,2-azo(2,4,4-trimethylpentane), 2,5-bis(tert-butylperoxy)-2,5-dimethylhexane, dicumyl peroxide, benzoyl peroxide, 2,2-bis(tert-butylperoxy)butane, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hex-3-yne, 1,1-bis(tert-butylperoxy)cyclohexane, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, tert-butylperoxy, di(tert-butyl)peroxy, and tert-butyl peroxybenzoate.
[0012] In one embodiment of the present invention, the resin composition further comprises: an inorganic filler, wherein the inorganic filler is selected from at least one of the group consisting of silicon dioxide, aluminum oxide, aluminum hydroxide, magnesium oxide, magnesium hydroxide, calcium carbonate, aluminum nitride, boron nitride, aluminum silicon carbide, silicon carbide, titanium dioxide, zinc oxide, zirconium oxide, barium sulfate, magnesium carbonate, barium carbonate, mica, talc and graphene.
[0013] In one embodiment of the present invention, the resin composition further comprises: a flame retardant, an inhibitor, a silane coupling agent, a surfactant, a toughening agent, a core-shell rubber, a light stabilizer, or a combination thereof.
[0014] Another object of the present invention is to provide a laminate comprising a resin substrate including a plurality of prepregs, each of the prepregs being made by coating a reinforcing material with a resin composition as described in the present invention; and a metal foil layer disposed on at least one surface of the resin substrate.
[0015] Another object of the present invention is to provide a printed circuit board comprising a multilayer board as described in the present invention.
[0016] One of the beneficial effects of the present invention is that the resin composition provided by the present invention can improve the appearance streaks, voids, etc. generated by using the prior art circuit board strip adhesive through the technical solution of "the crosslinking agent comprising 10 to 30 parts by weight of diisopropylbenzene crosslinking agent, and the diisopropylbenzene crosslinking agent being composed of 75% to 80% of 1,3-diisopropylbenzene and 20% to 25% of 1,4-diisopropylbenzene" and a specific formulation ratio. In addition, the specific formulation ratio of the present invention provides a better glass transition temperature (Tg) ≥180°C, a coefficient of thermal expansion in the XY direction ≤14 ppm / °C, a copper foil tensile strength (P / S) ≥3.0 lb / in, and a heat resistance tinning result >60 minutes, meeting the requirements of comprehensive performance.
Implementation Method
[0017] The technical solution adopted by the present invention is to provide a resin composition, wherein the total weight of the resin composition is 100 parts by weight, the resin composition comprising: (A) 20 to 40 parts by weight of unsaturated polyphenylene ether resin; (B) 5 to 15 parts by weight of styrene-butadiene-styrene copolymer; (C) 10 to 20 parts by weight of hydrogenated polyolefin resin; (D) 10 to 20 parts by weight of vinyl elastomer copolymer; and (E) 20 to 40 parts by weight of crosslinking agent; wherein the crosslinking agent comprises 10 to 30 parts by weight of diisopropylbenzene crosslinking agent, and the diisopropylbenzene crosslinking agent is composed of 75% to 80% of 1,3-diisopropylbenzene and 20% to 25% of 1,4-diisopropylbenzene.
[0018] Specifically, polyphenylene ether (PPE) resin possesses good mechanical properties and excellent dielectric properties, with a Dk / Df ratio of approximately 2.45 / 0.0007 at a frequency of 1 MHz, making it a preferred resin material for high-frequency printed circuit board substrates. Preferably, the unsaturated polyphenylene ether resin used in this invention is modified. More specifically, the unsaturated polyphenylene ether resin used in this invention can be a terminal vinyl benzyl modified polyphenylene ether resin or a difunctional methacrylate modified polyphenylene ether resin. Preferably, the unsaturated polyphenylene ether resin content is 20 to 40 parts by weight, i.e., a positive integer between 20 and 40. The number average molecular weight (Mn) of the polyphenylene ether compound is preferably 500 to 5000, more preferably 2000 to 4000. Excellent polyphenylene ether resins with a specific average molecular weight can provide better dielectric properties, heat resistance, and formability. If the molecular weight is less than 500, the finished product has poor heat resistance; if the molecular weight is greater than 5000, the flowability is poor and the melt viscosity is high. Examples of polyphenylene ether resins include SA-9000 (manufactured by SABIC, a polyphenylene ether compound with methacrylic groups) and OPE-2St 1200 (manufactured by Mitsubishi Gas Chemical, a polyphenylene ether compound with a styrene structure). Preferably, the polyphenylene ether resin of the present invention is a difunctional methacrylate-modified polyphenylene ether.
[0019] In one specific embodiment, the styrene-butadiene-styrene copolymer may be a polystyrene block copolymer and a polybutadiene block copolymer, for example, styrene thermoplastic elastomers produced by Asahi KASEI, with trade names T438, T439, P1500, L614, L617, etc. In a specific embodiment of the present invention, the hydrogenated polyolefin may include various hydrogenated styrene-butadiene-styrene triblock copolymers (also known as styrene-ethylene / butene-styrene copolymers) known in the art. The composition of the hydrogenated polyolefin resin is 10 to 20 parts by weight, i.e., a positive integer part by weight between 10 and 20. In one specific embodiment, the hydrogenated polyolefin resin is selected from at least one of the group consisting of hydrogenated styrene-butadiene-styrene triblock copolymers and hydrogenated styrene-butadiene-styrene triblock copolymers substituted with maleic anhydride. For example, hydrogenated polyolefins can be hydrogenated polyolefins produced by Asahi KASEI, with product models such as H1221, H1062, H1521, H1052, H1041, H1053, H1051, H1517, H1043, N504, H1272, M1943, M1911, and M1913.
[0020] Vinyl elastomer copolymers can improve the heat resistance of the cured resin composition and, through their own toughening properties, impart good physical properties to the cured resin composition, such as toughness and processability. Preferably, the vinyl elastomer copolymer is selected from at least one of the group consisting of polybutadiene, styrene-butadiene copolymer (SBR), styrene-butadiene-styrene block copolymer (SBS), polyisoprene, styrene-isoprene copolymer, styrene-isoprene-styrene block copolymer (SIS), acrylonitrile-butadiene copolymer, and acrylonitrile-butadiene-styrene block copolymer. The vinyl elastomer copolymer is present in an amount of 10 to 20 parts by weight, i.e., an integer part by weight between 10 and 20.
[0021] In a specific embodiment of the present invention, the resin composition comprises 20 to 40 parts by weight of a crosslinking agent, with a total weight of 100 parts by weight. Preferably, the ratio of crosslinking agent: rubber copolymer: unsaturated polyphenylene ether resin can be 3:3:4. More specifically, with a total weight of 100 parts by weight of the resin composition, the crosslinking agent comprises 10 to 30 parts by weight of a diisopropenylbenzene crosslinking agent, and the diisopropenylbenzene crosslinking agent is composed of 75% to 80% of 1,3-diisopropenylbenzene and 20% to 25% of 1,4-diisopropenylbenzene. The molecular weight of the crosslinking agent monomer is 158.24 g / mol. Preferably, the diisopropenylbenzene crosslinking agent is composed of 80% of 1,3-diisopropenylbenzene and 20% of 1,4-diisopropenylbenzene, and the specific crosslinking agent ratio can effectively reduce the aggregation of the resin composition.
[0022] In another specific embodiment of the present invention, the crosslinking agent may also include a vinyl crosslinking agent as needed, that is, the ratio of the diisopropylbenzene crosslinking agent and the vinyl crosslinking agent may be 2.9:0.1 to 1:2. For example, the ratio of the diisopropylbenzene crosslinking agent and the vinyl crosslinking agent may be 3:0, 2.9:0.1, 2:1 or 1:2.
[0023] More specifically, the vinyl crosslinking agent is selected from at least one of the group consisting of divinylbenzene (DVB), bis(vinylbenzyl) ether (BVBE), or 1,2-bis(vinylphenyl)ethane (BVPE). Preferably, the vinyl crosslinking agent is divinylbenzene (DVB) and / or 1,2-bis(vinylphenyl)ethane (BVPE). More preferably, the vinyl crosslinking agent is a combination of divinylbenzene and 1,2-bis(vinylphenyl)ethane. The vinyl crosslinking agent may be a commercially available option or may be prepared by known methods, which will not be described further here.
[0024] The free radical initiator may be an azo-type free radical initiator and / or a peroxide-type free radical initiator. For example, the free radical initiator may be azobisisobutyronitrile (AIBN), bis(2,4,4-trimethylpentan-2-yl)diazene, 2,5-bis(tert-butylperoxy)-2,5-dimethylhexane, dicumyl peroxide (DCPO), or benzoyl peroxide. The following are at least one of the following: peroxide, 2,2-bis(tert-butylperoxy)butane, 2,5-dimethyl-2,5-di(tert-butylperoxy)hex-3-yne, 1,1-bis(tert-butylperoxy)cyclohexane, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, tert-Butyl hydroperoxide, di-tert-butyl peroxide, and tert-butyl peroxybenzoate, or combinations thereof. Preferably, the free radical initiator is an azo-type free radical initiator. More preferably, the free radical initiator is 2,2-azo(2,4,4-trimethylpentane).
[0025] Specifically, if the proportion of free radical initiator is too high, the molecular weight of the cross-linked resin composition will be too low, resulting in poor physical properties. If the proportion of free radical initiator is too low, the reaction of the resin composition will be too slow, which is not conducive to future process applications.
[0026] Further, the resin composition of the present invention may, as needed, include: an inorganic filler selected from at least one of the group consisting of silicon dioxide, aluminum oxide, aluminum hydroxide, magnesium oxide, magnesium hydroxide, calcium carbonate, aluminum nitride, boron nitride, aluminum silicon carbide, silicon carbide, titanium dioxide, zinc oxide, zirconium oxide, barium sulfate, magnesium carbonate, barium carbonate, mica, talc, and graphene. Specifically, the inorganic filler can increase the thermal conductivity of the resin composition, improve its thermal expansion properties and mechanical strength.
[0027] Furthermore, the resin composition of the present invention may, as needed, include: flame retardant, inhibitor, silane coupling agent, surfactant, toughening agent, core-shell rubber, light stabilizer or a combination thereof.
[0028] Preferably, the flame retardant is a phosphorus-containing flame retardant and a brominated flame retardant. Examples of brominated flame retardants include ethylene-bis(tetrabromophthalimide), decabromodiphenyl ethane, and 2,4,6-tris(2,4,6-tribromophenoxy)-1,3,5-triazine. Examples of phosphorus-containing flame retardants include bisphenol diphenyl phosphate, ammonium polyphosphate, hydroquinone bis(diphenyl phosphate), bisphenol A bis(diphenyl phosphate), tris(2-carboxyethyl)phosphine (TCEP), tri(chloroisopropyl) phosphate, trimethyl phosphate (TMP), dimethyl methylphosphonate (DMMP), resorcinol bis(xylyl phosphate), phosphazene, melamine polyphosphate, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) and its derivatives or resins, melamine cyanurate, and trihydroxyethyl isocyanurate.
[0029] More specifically, flame retardants include phosphate esters, phosphonoenes, bis(diphenylphosphine oxide) oxides, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) flame retardants, and phosphonates. Specific examples of phosphate esters include condensed phosphate esters of dixylenyl phosphate. Specific examples of phosphonoenes include phenoxyphosphonene. Specific examples of bis(diphenylphosphine oxide) oxides include styryl bis(diphenylphosphine oxide). Specific examples of DOPO oxides include hydrocarbons (DOPO derivative compounds) having two DOPO groups in their molecules and DOPO having reactive functional groups. Specific examples of phosphonates include metal salts of dialkylphosphonates. The aforementioned flame retardants can be used individually or in combination of two or more. In one embodiment of the present invention, the flame retardant may be p-xylylbis(diphenylphosphine oxide), which improves the flame retardancy of the flame-retardant resin composition while enhancing its moisture resistance.
[0030] The inhibitor is a polymerization inhibitor, preferably tetramethylpiperidine oxide.
[0031] [Example]
[0032] Table 1 of the present invention provides the component ratios of the resin compositions of Examples 1 to 5 and Comparative Examples 1 to 3, respectively. Resin compositions were prepared according to each component ratio, and reinforcing materials were impregnated or coated onto the resin compositions using rollers. The resin compositions were then baked to evaporate the solvent, semi-cured, cooled, and wound to form semi-cured films. The semi-cured films were further subjected to hot-pressing to form a dielectric substrate layer. Specifically, the hot-pressing process involved stacking four semi-cured films and two 18 μm copper foils from the same batch in the order of copper foil, four semi-cured films, and copper foil. The stacks were then pressed under vacuum at 220°C for 2 hours to form a copper foil substrate, wherein the four semi-cured films cured to form an insulating layer between the two copper foils. The obtained finished products were further subjected to physical property tests, and the results are recorded in the table. The observations of the circuit board strip adhesives of Examples 1 to 5 and Comparative Examples 1 to 3 are shown in Figures 1A to 1H, respectively, and the SEM identification of the colloids is shown in Figures 2A to 2H, respectively.
[0033] [Physical Property Testing]
[0034] SEM identification of micelles: SEM images were used to observe whether resin agglomeration occurred, as shown in Figures 2A to 2H.
[0035] Glass transition temperature (Tg): The glass transition temperature of the metal foil substrate is measured using a dynamic mechanical viscoelastic analyzer (DMA). When the material passes through Tg, the storage modulus E' (Storage Modulus) will begin to decrease due to the movement of polymer chains, while the loss modulus E' (Loss Modulus) will increase. Finally, Tg is analyzed through the inflection point / inversion point of Tan Delta tan δ. The decrease in strength caused by the movement of polymer chains is used as a method for measuring Tg.
[0036] Coefficient of thermal expansion (XY-CTE): Measured according to the IPC-TM-650 test standard. Measured using thermomechanical analysis (TMA) with reference to IPC-TM-650.
[0037] Peeling strength (P / S) of copper foil: The measurement is performed according to the method described in IPC-TM-650 2.4.8. The force required for each test sample to pull the copper foil away from the surface of the substrate insulation layer is measured, and the unit is lb / in.
[0038] Copper foil laminate heat resistance (T288): also known as "tinning result", the heat resistance test is based on industry standard IPC-TM-650 2.4.24.1, which is the time required for the copper foil laminate to be immersed in a tin furnace at 288°C until the board bursts.
[0039] Table 1. Examples 1 to 5 and Comparative Examples 1 to 3 Product Name / Notes Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Comparative Example 2 Comparative Example 3 polyphenylene ether SA9000 30 30 30 30 30 30 30 30 Styrene-butadiene-styrene copolymer T439 10 10 10 10 10 10 10 10 Vinyl elastomer copolymer Ricon100 15 15 15 15 15 15 15 15 Hydrogenated polyolefin compounds H1053 15 15 15 15 15 15 15 15 Crosslinking agent IPAMS 30 20 10 10 29 50 0 0 DVB 0 10 20 10 0 0 30 0 BVPE 0 0 0 10 1 0 0 30 Flame retardant PQ60 =Resin*20% =Resin*20% =Resin*20% =Resin*20% =Resin*20% =Resin*20% =Resin*20% =Resin*20% free radical initiators VR-110 0.2 0.2 0.2 0.2 0.2 0.2 0.2 0.2 Inhibitors TEMPO 0.1 0.1 0.1 0.1 0.1 0.1 0.1 0.1 Inorganic packing SE0047 D50:2.4 =Resin*80% =Resin*80% =Resin*80% =Resin*80% =Resin*80% =Resin*80% =Resin*80% =Resin*80% SG @181C 280s 280s 250s 210s 270s 380s 90s <60s Circuit board filler @186C Normal appearance Normal appearance Normal appearance Normal appearance Normal appearance Exterior stripes Surface cavitation Surface cavitation SEM to identify micelles With / without resin agglomeration none ≤25um none ≤25um none ≤25um none ≤25um none ≤25um none ≤25um have 25um~50um It has a range of 50um to 100um. Thickness 0.80mm 0.80mm 0.80mm 0.80mm 0.80mm 0.80mm 0.80mm 0.80mm Tg 180 180 190 200 180 170 215 210 XY CTE DMA 12 12 14 10 12 13 15 17 P / S TMA 3.6 3.2 3.4 3.2 3.4 2.8 2.5 2.2 Solder Floating Hoz 60min 60min 60min 60min 60min 40min 10min 30min
[0040] SA-9000: Bifunctional methacrylate-modified polyphenylene ether (Mw: 2300, purchased from SABIC)
[0041] Vinyl crosslinking agents: commercially available diisopropylbenzene (IPAMS), divinylbenzene (DVB), bis(vinylphenyl)ethane (BVPE)
[0042] Free radical initiator: 2,2'-azobis(2,4,4-trimethylpentane) (purchased from Fujifilm Wako Chemical VR110)
[0043] Flame retardant: p-xylylbis(diphenylphosphine oxide) (PQ-60 purchased from Jin Yi Chemical Co., Ltd.)
[0044] Inhibitor: Commercially available 2,2,6,6-Tetramethylpiperidine-1-oxide (TEMPO).
[0046] Referring to Table 1, Comparative Example 1 used a higher proportion of diisopropylbenzene crosslinking agent, resulting in stripes on the appearance of the circuit board filler, a lower glass transition temperature (Tg), an SG of 380s which exceeded the optimal range (200-300s), lower copper foil tensile strength (P / S), and the tinning results did not meet the standard.
[0047] Comparative Examples 2 and 3 used a single crosslinking agent (vinyl crosslinking agent). Even though the reaction was faster and the glass transition temperature (Tg) was higher, referring to Figures 1G and 1H, the circuit board filling produced voids, and the SEM analysis of Figures 2G and 2H showed resin agglomeration of 25um-50um. The SG value was low, the coefficient of thermal expansion was high, and the tensile strength to the copper foil was low. The tinning results were also less than 60 minutes, which did not meet the standard.
[0048] Compared to the comparative example, Examples 1 to 5 using diisopropylbenzene crosslinking agent showed normal appearance of the circuit board filler, and Figures 2A to 2E also showed no resin agglomeration, glass transition temperature greater than 180°C, coefficient of thermal expansion of metal foil substrate in XY direction ≤ 14 ppm / °C, and the metal foil substrate of the present invention has a copper foil tensile force (P / S) ≥ 3.0 lb / in.
[0049] Example 1 shows that using only diisopropylbenzene crosslinking agent, the circuit board filler has a normal appearance, no resin agglomeration, and its overall performance meets the standard requirements. Examples 2, 3, and 5 use a combination of diisopropylbenzene crosslinking agent and vinyl crosslinking agent; the circuit board filler has a normal appearance, no resin agglomeration, and its overall performance also meets the standard requirements. Example 4 shows that the circuit board filler has a normal appearance, no resin agglomeration, and its overall performance is optimal. The ratio of diisopropylbenzene crosslinking agent to vinyl crosslinking agent is 1:2, and the ratio of diisopropylbenzene crosslinking agent:DVB:BVPE is 1:1:1.
[0050] The beneficial effects of the present invention are that the resin composition, laminate, and printed circuit board provided by the present invention can improve the appearance streaks, voids, etc., generated by using the existing circuit board strip adhesive through the technical solution of "the crosslinking agent includes 10 to 30 parts by weight of diisopropylbenzene crosslinking agent, and the diisopropylbenzene crosslinking agent is composed of 75% to 80% of 1,3-diisopropylbenzene and 20% to 25% of 1,4-diisopropylbenzene" and a specific formulation ratio, and eliminate the formation of resin agglomeration as determined by SEM. In addition, the specific formulation ratio of the present invention provides a better glass transition temperature (Tg) ≥180°C, a coefficient of thermal expansion in the XY direction ≤14 ppm / °C, a copper foil tensile strength (P / S) ≥3.0 lb / in, and a heat resistance tinning result >60 minutes, meeting the requirements of comprehensive performance.
[0051] The above description is only a preferred embodiment of the present invention and does not limit the patent scope of the present invention. Therefore, all equivalent changes made using the content of the present invention are also included in the scope of the present invention and are hereby stated. [Simplified Explanation of the Diagram]
[0052] Figure 1A is an observation diagram of the strip adhesive on the circuit board, Example 1.
[0053] Figure 1B is an observation diagram of the circuit board strip adhesive, Example 2.
[0054] Figure 1C is an observation diagram of the circuit board strip adhesive, Example 3.
[0055] Figure 1D is an observation diagram of the circuit board strip adhesive, Example 4.
[0056] Figure 1E is an observation diagram of the circuit board strip adhesive, Example 5.
[0057] Figure 1F is a comparative example 1 of the observation diagram of the strip adhesive on the circuit board.
[0058] Figure 1G is a comparative example 2 of the observation diagram of the strip adhesive on the circuit board.
[0059] Figure 1H is a comparative example 3 of the observation diagram of the strip adhesive on the circuit board.
[0060] Figure 2A is a schematic diagram of SEM identification of micelles in Example 1.
[0061] Figure 2B is a schematic diagram of SEM identification of micelles in Example 2.
[0062] Figure 2C is a schematic diagram of SEM identification of micelles in Example 3.
[0063] Figure 2D is a schematic diagram of SEM identification of micelles in Example 4.
[0064] Figure 2E is a schematic diagram of SEM identification of micelles in Example 5.
[0065] Figure 2F is a comparative example 1 of SEM micelle discrimination schematic diagram.
[0066] Figure 2G is a comparative example 2 of SEM micelle identification schematic diagram.
[0067] Figure 2H is a comparative example 3, which is a schematic diagram of SEM identification of micelles.
Claims
1. A resin composition comprising, in a total weight of 100 parts, of: 20 to 40 parts by weight of an unsaturated polyphenylene ether resin; 5 to 15 parts by weight of a styrene-butadiene-styrene copolymer; 10 to 20 parts by weight of a hydrogenated polyolefin resin; 10 to 20 parts by weight of a vinyl elastomer copolymer; and 20 to 40 parts by weight of a crosslinking agent; wherein, The crosslinking agent comprises 10 to 30 parts by weight of diisopropylbenzene crosslinking agent, wherein the diisopropylbenzene crosslinking agent is composed of 75% to 80% of 1,3-diisopropylbenzene and 20% to 25% of 1,4-diisopropylbenzene; wherein the unsaturated polyphenylene ether resin is a terminal vinyl benzyl modified polyphenylene ether resin or a difunctional methacrylate modified polyphenylene ether resin, and its molecular weight (Mn) is 500 to 5000.
2. The resin composition as claimed in claim 1, wherein, The crosslinking agent may include a vinyl crosslinking agent as required, and the ratio of the diisopropylbenzene crosslinking agent to the vinyl crosslinking agent is from 2.9:0.1 to 1:
2.
3. The resin composition as claimed in claim 2, wherein, The vinyl crosslinking agent is selected from at least one of the group consisting of divinylbenzene, divinylbenzyl ether, or 1,2-bis(vinylphenyl)ethane.
4. The resin composition as claimed in claim 1, wherein, The hydrogenated polyolefin resin is selected from at least one of the group consisting of hydrogenated styrene-butadiene-styrene triblock copolymers and hydrogenated styrene-butadiene-styrene triblock copolymers substituted with maleic anhydride.
5. The resin composition as claimed in claim 1, wherein, The vinyl elastomer copolymer is selected from at least one of the group consisting of polybutadiene, styrene-butadiene copolymer (SBR), styrene-butadiene-styrene block copolymer (SBS), polyisoprene, styrene-isoprene copolymer, styrene-isoprene-styrene block copolymer (SIS), acrylonitrile-butadiene copolymer, and acrylonitrile-butadiene-styrene block copolymer.
6. The resin composition as claimed in claim 1, further comprising: A free radical initiator selected from at least one of the group consisting of azobisisobutyronitrile, 2,2-azo(2,4,4-trimethylpentane), 2,5-bis(tert-butylperoxy)-2,5-dimethylhexane, dicumyl peroxide, benzoyl peroxide, 2,2-bis(tert-butylperoxy)butane, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hex-3-yne, 1,1-bis(tert-butylperoxy)cyclohexane, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, tert-butylperoxy, di(tert-butyl)peroxy, and tert-butyl peroxybenzoate.
7. The resin composition as claimed in claim 1, further comprising: An inorganic filler, wherein the inorganic filler is selected from at least one of the group consisting of silicon dioxide, aluminum oxide, aluminum hydroxide, magnesium oxide, magnesium hydroxide, calcium carbonate, aluminum nitride, boron nitride, aluminum silicon carbide, silicon carbide, titanium dioxide, zinc oxide, zirconium oxide, barium sulfate, magnesium carbonate, barium carbonate, mica, talc and graphene.
8. The resin composition as claimed in claim 1, further comprising: Flame retardants, inhibitors, silane coupling agents, surfactants, toughening agents, core-shell rubbers, light stabilizers, or combinations thereof.
9. A laminated plate comprising: A resin substrate comprising a plurality of precured films, each of the precured films being made by coating a reinforcing material with a resin composition as described in claim 1; and a metal foil layer disposed on at least one surface of the resin substrate.
10. A printed circuit board comprising a multilayer board as described in claim 9.
